ANALISIS PERPINDAHAN PADA STRUKTUR BANGUNAN MENGGUNAKAN BASE ISOLATOR DI WILAYAH GEMPA KUAT - Muliadi Muliadi; Mochammad Afifuddin; T. Budi Aulia (Politeknik Negeri Lhokseumawe, 2017)
The meeting of three major tectonic plates makes Indonesia prone to earthquakes, be it the Indo-Australian plate, the Eurasian plate, and the Pacific plate. Earthquakes are caused by the release of energy generated by the pressure caused by moving plates. Its essence is not earthquake that damage building but anticipation of building which must be in earthquake resistant design. In this case, the building structure must be designed to be earthquake resistant. One of earthquake resistant building technology is technology with base isolator system. This study aims to determine the displacement analysis that occurs due to the effects of earthquake on the structure of the building. Both in the use of base isolator and without using base isolator. The design of this structure is done by analyzing the time dynamic history load in the SRPMK building (struktur rangka pemikul momen khusus). With 10 storey floor building, regular shape, in SRPMK building. The structural elements reviewed in analyzing the displacement of the building structure are in a column, either for fixed base building of SRPMK or for SRPMK building with base isolator. Data analysis is done by using SAP2000 computer software. The result of analysis shows that the maximum fixed column SRPMK structure building structure on the 3rd floor reaches 27.97 mm from the base of the SRPMK fixed base. While at the base of the isolator there is a displacement of 5.79 mm from the base of SRPMK base isolator. The result of analysis shows that the building of SRPMK base isolator compared with SRPMK building, the value of displacement of final floor level structure (floor 10) can be reduced to 15.85%. Application of base isolator in this case can be used as its function can reduce earthquake load.Keyword : base isolator, displacement, SRPMK; analysis of time history.